Nebulizer – In vitro Bioequivalence testing requirements: A review - Prajapati, Shubham; Saha, Sanjay; Shambulingappa, B; Ch., Dilip Kumar; Sahoo, Bikash (Asian Journal of Pharmaceutical Research and Development, 2020)
Generic Nebulized aerosol is often perceived as inferior to their branded counterparts; however, they are safe and effective if they can meet the regulatory requirements. International regulatory agencies have developed recommendations and guidance for bioequivalence approaches of orally inhaled drug products (OIDPs) for local action. The objective of this article is to discuss the approaches can be used for to show bioequivalence requirement for Food and Drug Administration (FDA) in the United States of America (USA) with reference product. This review endorsed that inhalation solutions and suspensions undertaken to determine the drug substance delivery rate, total drug substance delivered and Aerodynamic assessment of nebulized aerosols [aerodynamic particle size distribution (APSD)/droplet size distribution (DSD)].These are the most important parameters in characterization, evaluation and bioequivalence studies of nebulizers. These devices operate continuously; once loaded and require little or no co-ordination on the part of user they proved that these devices suitable for weak, pediatric or geriatric patients. The regulatory agencies declared that; there is no specific requirements testing in case of nebulizers like Metered dose inhalers (MDI) and Dry powder inhalers (DPIs). In United States of America (USA) regulation falls under the auspices of centre for devices and radiological health (CDRH), and new devices require 510(k) premarket notification. This review outlines all the bioequivalence test parameter.